Análisis, Diseño y Ejecución de un Control de Costos Reales para un Proyecto de Construcción - Rojas-Campos, Emanuel (Instituto Tecnológico de Costa Rica, 2007)
The developed work consists, in first instance, evaluating the existing methodology for the control of costs, in a construction company and, to determine thus; if this mechanism provides useful information that it allows to opportunely diagnose and to correct the course of the project. Once concluded this phase, and of to have made the recommendations pertinent; it is tried to design a programmed tool that, in addition to functional, is from easy manipulation and helps of this form in workings such as: to introduce the field data and to make the interpretation more accessible of the successfully obtained information. Consequently, this methodology will make agile the control, the analysis of the advance of the work and the costs of the project. The design of the tool was elaborated with Microsoft Excel, for the creation of tables of storage of data and with the aid of Macros in Visual BASIC, for the assembly of screens. The objective must to implement the created tool, in a real project of construction. The used mechanism will be to elaborate a monthly report, that includes the aspects and indices contemplated in the important tool and other parameters for the control of costs; in addition, it has been made the revision and study of legal documents; another aspect taken into account is the initial preparations for the correct planning and putting in practices of the project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción).Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2007.
Keywords: Control de costos; Microsoft excel; Evaluación; Sistemas de control; Planeación